Periodization: theory and methodology of training - Bompa, T. O.; Haff, G. G. (Human Kinetics, 2009)
Since the introduction of this groundbreaking training theory by Tudor O. Bompa in 1963, periodization has become the basis of every serious athlete`s training. Now in its fifth edition, Bompa`s classic text combines the concepts central to periodization and training theory with contemporary advances in sport science, physiology, and coaching.